2007
DOI: 10.1128/jvi.02564-06
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Human Immunodeficiency Virus Type 1 (HIV-1) Nef-Specific T Cells Recognizing Multiple Variants in Early HIV-1 Infection

Abstract: A human immunodeficiency virus (HIV)-preventive vaccine will likely need to induce broad immunity that can recognize antigens expressed within circulating strains. To understand the potentially relevant responses that T-cell based vaccines should elicit, we examined the ability of T cells from early infected persons to recognize a broad spectrum of potential T-cell epitopes (PTE) expressed by the products encoded by the HIV type 1 (HIV-1) nef gene, which is commonly included in candidate vaccines. T cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 45 publications
4
58
3
Order By: Relevance
“…Single-peptide-based screening of T-cell responses allowed fine mapping, which revealed broad crossclade T-cell populations, although clade-specific magnitude, breadth, and domain targeting were observed. Immunodominance of the Nef central region was demonstrated in our cohort, in accordance with other studies (22,26,28,35,43,45). Most of the cross-reactive peptides clustered in this conserved region of the protein.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Single-peptide-based screening of T-cell responses allowed fine mapping, which revealed broad crossclade T-cell populations, although clade-specific magnitude, breadth, and domain targeting were observed. Immunodominance of the Nef central region was demonstrated in our cohort, in accordance with other studies (22,26,28,35,43,45). Most of the cross-reactive peptides clustered in this conserved region of the protein.…”
Section: Discussionsupporting
confidence: 79%
“…2A and B). This observation has also been reported previously for subtype B and other subtypes (22,26,28,35,43,45). However, in this study, clade-specific differences in targeted Nef domains were observed.…”
Section: Study Subjectscontrasting
confidence: 54%
See 2 more Smart Citations
“…The PTE approach is based on a biometric algorithm that includes frequently found kmer sequences from circulating strains in a sequence database to build a standardized panel of HIV peptides for CTL based vaccine evaluation (35). Similarly to the toggled peptides, PTE peptides detect significantly more and stronger responses than consensus based peptides (36). Toggled peptides and PTE peptides each have different virtues and issues.…”
Section: Discussionmentioning
confidence: 99%